Impact of wave-current interaction on Hurricane Ian storm surge simulation - Sieu-Cuong San; Yonggang Liu; Haibo Xu; Robert H. Weisberg; Sebin John; Kaili Qiao; Jason A. Law; Lianyuan Zheng; Steven A. Murawski; Sherryl Gilbert; Gary T. Mitchum; Thomas K. Frazer; et al. (Ocean Modelling, 2026)

Winter convective mixing regulates oceanic C : N : P ratios - Deepika Sahoo; Himanshu Saxena; Sipai Nazirahmed; Mohammad Atif Khan; Deepak Kumar Rai; Niharika Sharma; Sebin John; Sanjeev Kumar; A. K. Sudheer; Ravi Bhushan; Arvind Singh (Limnology and Oceanography, 2024)
Recent studies have challenged the validity of the Redfield ratio. It is proposed that physical and biogeochemical processes govern the geographical variations in carbon : nitrogen : phosphorus (C : N : P) ratios. However, this proposal remains to be examined through concurrent observations of C : N : P ratios with physical and biogeochemical processes in various marine reservoirs. Here, we sampled the Arabian Sea for its C, N, and P content in organic and inorganic pools during the winter monsoon. We analyzed the role of convective mixing, eddies, and N 2 fixation to explain the variation in observed elemental ratios. Convective mixing injected the cold water and enhanced the supply of N and P nutrients in the top layer (surface to 50–75 m) of the northern Arabian Sea. This led to a decrease in the N : P and C : P ratios in the particulate organic matter in the northern region, but C : N : P increased equatorward, averaging 245 : 32 : 1 in the top layer of the Arabian Sea. The variation in the elemental ratios in the top layer is best explained by the changes in water temperature. N 2 fixation contributed negligibly to the N : P ratio of the export flux. The substantial decrease in N : P ratios of nutrients in the subsurface waters is most likely caused by the denitrifying conditions in the Arabian Sea. As the processes of convective mixing and eddies are are prevalent oceanic processes, our observations underpin that the interplay of these processes leads to changes in the elemental ratios globally.

Short-term forecast of Karenia brevis trajectory on the West Florida Shelf - Yonggang Liu; Robert H. Weisberg; Lianyuan Zheng; Katherine A. Hubbard; Eric G. Muhlbach; Matthew J. Garrett; Chuanmin Hu; Jennifer P. Cannizzaro; Yuyuan Xie; Jing Chen; Sebin John; Laura Y. Liu (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Input-export fluxes of heavy metals in the Cochin estuary, southwest coast of India - Kalathingal Ramkollath Lallu; Sebin John; Kallungal Ravunnikutty Muraleedharan; Thundiyil Raju Gireeshkumar; Pallikkoottathil Balakrishnan Udayakrishnan; Dayana Mathew; Sachin Mathew; Chennicheri Revichandran; Maheswari Nair; Perunninakulath Subrayan Parameswaran; Kizhakkepatt Kalathil Balachandran (Environmental Science and Pollution Research, 2023)

Are Artificial Barrages Necessary to Prevent Saline Incursion? A Modelling Approach to Restore the Healthy Ecosystem of the Vembanad Lake - Sebin John; C. Revichandran; K. R. Muraleedharan; G. Seena; S. Guatham; B. Srijith; S. Abdul Azeez; Pierre Cazenave (Environmental Modeling & Assessment, 2022)

A study to improve the fog/visibility forecast at IGI Airport, New Delhi during the winter season 2020–2021 - S H Arun; Charan Singh; Sebin John; Sumant Kumar Diwakar; Dinesh Kumar Sankhala; Narendra Nigam; Chander S Tomar; Gajendra Kumar (Journal of Earth System Science, 2022)

Time-dependent plume front positioning and its dynamics coupled with seasonal river efflux - G. Seena; K. R. Muraleedharan; C. Revichandran; S. Abdul Azeez; Sebin John; Ravikumar C. Nair (Ocean Dynamics, 2022)

Sound speed variation in the coastal waters off Cochin and signature of subsurface maxima - Abdul Azeez S; Revichandran C; Muraleedharan K. R; Sebin John; Seena G; Ravikumar C. Nair; Manju K. G (Ocean Dynamics, 2021)

Correction to: Formation Mechanism of Mud Bank Along the Southwest Coast of India - K. R. Muraleedharan; P. K. Dinesh Kumar; S. Prasanna Kumar; Sebin John; B. Srijith; K. Anil Kumar; K. Naveen Kumar; S. Gautham; V. Samiksha (Estuaries and Coasts, 2018)

Formation Mechanism of Mud Bank Along the Southwest Coast of India - K. R. Muraleedharan; P. K. Dinesh Kumar; S. Prasanna Kumar; Sebin John; B. Srijith; K. Anil Kumar; K. Naveen Kumar; S. Gautham; V. Samiksha (Estuaries and Coasts, 2018)